The Difference Effect of Special Cervical Collar with Height of 5 cm and 6 cm to Reduce Neck Pain among Students in Karanganyar, Central Java - Alfan Zubaidi; Arif Fadli (Indonesian Journal of Medicine, 2022)
Background: Specific cervical collars need to be standardized in order to effectively and efficiently reduce cervical syndrome pain. This condition occurs because the radicle vertebrae are compressed in the long term and even pain can radiate to both shoulders and even to the arches of both hands, this condition will result in abnormal and rapid fatigue. The purpose of this study was to find a standardized cervical collar design specifically to reduce cervical syndrome pain in Tahfidz Karanganyar Islamic boarding school students.Subjects and Method: This was a Randomized Control Trial (RCT) study which was con-ducted from March 2022 to August 2022 in all Tahfidz Islamic boarding schools in Karang-anyar, Central Java, Indonesia. The sample in this study were 160 students with cervical syndrome. Each group in this study consisted of 80 students who were divided into control and treatment groups using simple random sampling. The dependent variable in this study is neck pain (cervical syndrome). The independent variable is the use of the cervical collar. Data analysis uses the Independent samples t-test if the data is normal, and uses the Mann Whitney test if the data is not normal.Results: After the intervention was given, the results showed that the average pain in the intervention group using a special collar as high as 6 cm (Mean = 1.11; SD = 0.39) was lower in pain compared to the control group using a special collar as high as 5 cm (Mean = 3.50; SD = 0.57) and statistically significant (p<0.001).Conclusion: The use of a special cervical collar with a height of 6 cm is more effective in reducing pain than a special cervical collar with a height of 5 cm.Keywords: cervical syndrome, cervical collar, special cervical collar with a height of 6 cm and 5 cm.Correspondence: Alfan Zubaidi. Department of Orthotic Prosthetic, Ministry of Health Surakarta. Jl. Letjen Sutoyo, Mojosongo, Surakarta, Central Java, Indonesia. Email :drsalfanzubaidi@gmail.com.Indonesian Journal of Medicine (2022), 07(04): 411-416https://doi.org/10.26911/theijmed.2022.07.04.06